The Radiological Evaluation of Posterior Superior Alveolar Artery by Using CBCT - Karslioglu, Hazal; Çitir, Mesude; Gunduz, Kaan; Kasap, Pelin (Current Medical Imaging, 2021)
Background: Evaluation of the maxillary sinus anatomy prior to sinus lift procedures is important to avoid surgical complications due to the close anatomical relationship between the posterior maxillary region and the maxillary sinüs. Introduction: In order to avoid traumatizing the posterior superior alveolar artery and to prevent perioperative bleeding, locating the exact position of the artery is imperative before the surgical procedures. Methods: 150 CBCT scans were evaluated. The distance from the inferior border of the PSAA to the alveolar crest (the vertical line from the artery to the crest) and floor of the maxillary sinus, the distance from PSAA to medial sinus wall, nasal septum, zygomatic arch, position, the distance from the floor of maxillary sinüs to the alveolar crest and diameter of the PSAA were assessed. Locations of the artery were classified. Results: The artery diameters were mostly ≥ 1 mm. The artery was mostly intraosseous (59.7%), 21.7% was superficial and only 18.7% was intra-sinuscular. Conclusion: The location of PSAA is intraosseous in most patients. The artery diameters were mostly ≥ 1 mm and we can say that increasing the size also increases the risk of complications.
Keywords: Cone beam computed tomography